Data mining algorithms 2 - Witten, Ian (Henry Stewart Talks, 2008)
Linear models, Classification by regression, Support vector machine, Multilayer perceptron, Trees for numeric prediction, Instance based learning and clustering, Hierarchical clustering, Iterative: fixed num of clusters, Probabilistic clustering, Using and extending the mixture model, Bayesian clustering, Engineering the input and output, Attribute selection, Data transformations, Principal component analysis, Combining multiple models, Bagging, Randomization, Boosting, Stacking, Using unlabeled data, Co-training
Archived at 2022/03/17